Inter- and intra-observer reliability of thoracic limb circumference measurement methods in sound dogs - Deabold, Kelly; Harriz, Jordan; Madeiros, Brandy; Davies, Wendy; Shmalberg, Justin; Miscioscia, Erin (Frontiers in Veterinary Science, 2023)
Objective: The primary objectives of this study are to (1) compare the inter- and intra-observer reliability of thoracic limb circumference measurement methods in sound dogs, and (2) determine the most reliable thoracic limb positioning and location on the thoracic limb for performing circumferential measurements. Methods: Thoracic limbs of 10 apparently sound dogs (20 limbs) were blindly and independently measured by 3 observers. Triplicate measurements were performed at 50% and 70% brachial (Br) length (length between the greater tubercle and lateral humoral epicondyle) and 25% ABr length (length between the lateral humeral epicondyle and ulnar styloid process), both with the elbow extended and at an approximate weight-bearing (WB) angle. Intra-class correlation coefficients (ICC) with a 95% confidence interval (CI) were used for data analysis with a p < 0.05 being significant. Results: All measures had significantly good to excellent intra- (ICC 0.836 – 0.994, p < 0.001) and inter-observer reliability (ICC 0.834 – 0.996, p < 0.001). Inter-observer reliability was excellent at 25% ABr extended and WB positions, and at 50% Br WB position, with a wider confidence interval at the latter location. Intra-observer reliability was excellent across all observers for 25% ABr extended and WB, and 50% Br WB positions, also with a wider confidence interval at the latter location. Conclusion: Circumferential measurement of the canine thoracic limb was most reliable at 25% ABr length with the elbow either in an extended or WB position.